The Study on Balancing Factor Between Women Rights and Religious Constraints During Menstruation - B, LEELESH SUNDARAM; JAYAPRAKAS, CHITRA; V, VISHNU PRIYA; R, GAYATHRI. (The journal of contemporary issues in business and government, 2020)
As judgment in the Sabarimala case enabled the right of worship and religious practices of women, still a large sect of the society up hold the religious factors and principles. Various instances reported by social media prove that agitation lies in respect to entry of women into temple shrine. an ambiguity arises with respect to the balancing point between the religious rights and menstruating women at the same time When a close understanding of the cultural practices of menstruating women and the verdict in Sabrimala case is made, though the practices of religious constraints against menstruating women is an antiquity custom, an absurdity prevails with respect to its validity in the current century.. This research aims in identifying what is the balancing point between the religious rights of women and constraints during menstruation. With the help of non probability convenience sampling with a sample size of 1758 and using chi square and correlation test it could be found out that there is no relationship between Public opinion on Acceptance of religious constraints during menstruation and occupation. This helps in framing the conclusion that policy policy acts as a balancing point between women rights and constraints during menstruation. The paper gives a recommendation as that judiciary must give rationales governing individual statements and prospective while rendering judgments.